The Effect Of Service Quality And Price On Customer Loyalty With Customer Satisfaction As An Intervening Variable At Pt Azzahroni Syifa Tour (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
In the increasingly fierce competition, Umrah bureaus are not only required to offer competitive services, but also build long-term relationships with customers through customer satisfaction and loyalty. This study aims to determine the factors that influence customer satisfaction and loyalty. A total of 96 samples were taken for data collection. Quantitative research methods were applied to the study and aimed to test the causal influence between variables. The research data was analysed using the SEM PLS (Partial Least Squares Structural Equation Modeling) method. The results showed that there is an effect of service quality on customer satisfaction with a P-value of 0.08, so the first hypothesis can be accepted. Price has an effect on customer satisfaction with a P-value of 0.026. Customer satisfaction has no effect on customer loyalty with a P-value of 0.065. Service quality affects loyalty with P-values of 0.015. Price has no effect on customer loyalty with P-values of 0.057. Meanwhile, testing the indirect effect through customer satisfaction as an intervening variable shows that customer satisfaction is not able to become an intervening variable that mediates the effect of service quality and price because each has a P-value of 0.123 and 0.30.
Keywords: Customer satisfaction; service quality; price; customer loyalty